Implementation of a ROS 2-Based Differential Robot Drive System in a Robot Control System - Ivan Rivaldo Butarbutar; Roni Permana Saputra; Hendrana Tjahjadi (International Enterprise Integration Association, 2026)
This study aims to develop and evaluate a ROS2-based differential-drive robot control system using a low-cost embedded robotic architecture consisting of a Raspberry Pi 4 and Arduino Nano. The proposed system redesigns the previous robot architecture by simplifying the embedded controller configuration from multiple microcontrollers into a single Arduino Nano integrated with dual independent BLDC motor drivers. The system utilizes ROS2 communication topics including /cmd_vel, /target_rpm, /wheel_rpm, and /odom to enable real-time motion control, wheel speed feedback, and odometry estimation. Motor control is implemented using a GP8503 DAC module and ZS-X11H motor drivers, while wheel RPM feedback is acquired using rotary encoders. Experimental results show that the robot is capable of performing real-time differential-drive motion and successfully generating real-time wheel RPM feedback and odometry information. However, deviations of approximately 40–45% between target RPM and actual RPM were observed due to the absence of PID-based wheel speed correction, wheel slip, and mechanical load imbalance and motor nonlinearity. This research demonstrates the successful integration of ROS2 middleware with a simplified low-cost embedded robotic architecture as a foundation for future autonomous navigation and localization development.